Promoting Community Renewable Energy as a tool for Sustainable Development in Rural Areas of Thailand - Chatchawan Chaichana (2018)
© 2017 The Authors. Published by Elsevier Ltd. Community Renewable Energy (CRE) projects is being promoted in many countries as well as in Thailand. This research investigated the benefits of CRE projects that were promoted by the Ministry of Energy of Thailand. Data from 26 CRE projects has been analyzed. It was found that there are 6 types of renewable energy that are used in the CRE projects. The most popular types of renewable energy are Biogas (12 projects) and Solar thermal (7 projects). Most of the projects are located in Northern and Southern of Thailand, 11 and 9 projects respectively. It is expected that the 26 CRE projects can produce 845 kW of thermal energy and 86 kW of electricity Direct benefits of CRE project. The project size ranges from 0.1 -5.1 Million THB (3,000-160,000 USD), in average 1.3 Million THB (40,000 UDS) per project. Total project value of all 26 projects were 34.5 Million THB (1,078,000 USD). The total co-investment from the Ministry of Energy were 20.3 Million THB (634,000 USD) or approximately 60% of the total project value. There are 1,638 households involved in the CRE projects. The CRE projects could either generate income or save expense worth approximately 5,530,000 THB (173,000 USD) per year. Several CRE projects can contribute to environment protection as well.